Role Model Approach, Community Dialogue Sessions And Changes In Traditional Fatherhood Practice In Rural Bangladesh - Imtiaz, Sayed Saikh; Begum, Afsana (2016)
This paper aims to discuss the effectiveness of the role model approach in community dialogue session to initiate self-reflection among young fathers for changing the traditional fatherhood practices to prevent violence at the household in rural Bangladesh. Using the qualitative method of data collection the research evaluate a community dialogue mechanism involving fathers who have children aged between 0 to 5 years and who got the opportunity to interact with the ‘role model’ fathers. The first part of the paper discusses about the background and context of organizing the role model mechanism and the community dialogue session. This section describes the role model mechanism that works as a process to persuade the fathers in the community dialogue session. Here the paper gives a brief account of the role model fathers who have successfully challenged the traditional harmful fatherhood norms and therefore contributed to the women empowerment. The second part gives specific case studies on fathers who participated in the community dialogue session and became motivated and participated in the care work in the household level. The third part of the paper discusses on the outcome of the fathers participation in the care work in relation to violence prevention and the practice of good parenting techniques at the household level. The paper ultimately concludes, role model techniques together with the community dialogue session would ultimately challenge the traditional ideology of fatherhood and resist the enactment of violence in household level.